The Influence Of Work Life Balance And Compensation On Employee Performance With Employer Branding As A Moderating Variable - Rahmatulloh, Titik Nur; Buniarto, Edwin Agus; Muttaqien, Zaenul (Jurnal Mamangan, 2023)
This study aims to test and analyze the effect of work life balance and compensation on employee performance with employer branding as a moderating variable on Gen Z in Kediri City. This type of research is quantitative research with non-probability sampling method and purposive sampling technique. The sample used was 100 respondents who are Gen Z in Kediri City who work as employees. Data was collected using a questionnaire method distributed online via google form. The analysis method used is Partial Least Square (PLS) with the help of SmartPLS software. The results showed that work life balanced has a negative and significant effect on employee performance at gen z in Kediri City. Compensation has a positive and significant effect on employee performance at gen z in Kediri City. Work life balanced has a negative and significant effect on employee performance with employer branding as a moderating variable on gen z in Kediri City. Compensation has a positive and significant effect on employee performance with employer branding as a moderating variable on gen z in Kediri City.